Analysis in the motivation of the students of physical education study program, faculty of sport and health sciences, universitas negeri yogyakarta in their career choice - Dinka Salfa Zahira; Hardopo Putro, Kukuh; Yoga Sampurna; Thohiroh Anisah Samaah; Silvester Ezra Putra Ginting; Alfahri Ikhsan Banurea; Adi Wibisono; Nayla Anindya Putri; Alya Dwi Rizqika; Egia Peulisanti PA; Farrel Al Buchori Yusnani (Jorpres (Jurnal Olahraga Prestasi), 2025)
This research aims to: (1) ascertain the motivations of students enrolled in the Physical Education Study Program, Faculty of Sport and Health Sciences, Universitas Negeri Yogyakarta (FIKK UNY) for the classes of 2024, 2023, and 2022; (2) identify the career aspirations of students in the Physical Education Study Program, Faculty of Sport and Health Sciences, Universitas Negeri Yogyakarta for the classes of 2024, 2023, and 2022; and (3) analyze the correlation between students motivation in the Physical Education Study Program, Faculty of Sport and Health Sciences, Universitas Negeri Yogyakarta and their career choices.This research was a descriptive quantitative analysis by utilizing the simple random sampling technique. This research employed the survey approach. The research subjects comprised of students from the Physical Education Study Program, Faculty of Sport and Health Sciences, Universitas Negeri Yogyakarta: Class D of 2024, Class A of 2023, and Class B of 2022, totaling 152 individuals. The data collection utilized a questionnaire administered to 152 research participants. The employed data analysis technique was descriptive analysis, represented in percentages.The findings of this research indicate that: (1) the motivation levels of students enrolling in the Physical Education Study Program FIKK UNY for the 2024, 2023, and 2022 cohorts are classified as very high for 53.3% of 81 students, high for 30.9% of 47 students, medium for 11.2% of 17 students, low for 2.6% of 4 students, and very low for 2% of 3 students; (2) The career aspirations of students in the Physical Education Study Program, Faculty of Sport and Health Sciences, Universitas Negeri Yogyakarta encompass 152 students, with a cumulative score reflecting a 100% representation of sports coaching outcomes. 76.3% of 116 students are fitness instructors. 23.6% of 36 students are sports consultants. 27.6% of 42 students are sports writers. 21.7% of 33 students are managers of sports facilities and infrastructure. 25.6% of 39 students are physical therapists, 18.4% of 28 students are sports referees, 43.4% of 66 students pursue further studies/Master Program, 39.4% of 60 students are enrolled in Teacher Professional Education (PPG), 48.6% of 74 students are entrepreneurs, 15.7% of 24 students are in Armed Forces and Police, and 38.8% of 59 students are employed. The correlation between intrinsic motivation and career is very low and negative, while the correlation between extrinsic motivation and career is very low and positive